2014 IEEE 27th Computer Security Foundations Symposium 2014
DOI: 10.1109/csf.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

How Task Familiarity and Cognitive Predispositions Impact Behavior in a Security Game of Timing

Abstract: This paper addresses security and safety choices that involve a decision on the timing of an action. Examples of such decisions include when to check log files for intruders and when to monitor financial accounts for fraud or errors. To better understand how performance in timing-related security situations is shaped by individuals' cognitive predispositions, we effectively combine survey measures with economic experiments. Two behavioral experiments are presented in which the timing of online security actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In contrast, average risk-seeking individuals benefit strongly from a high NFC and suffer considerably from a low NFC. 4 This effect is particularly strong for Study 1 (see Figure 9b).…”
Section: Interaction Effect Of Risk Propensity and Need For Cognitionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, average risk-seeking individuals benefit strongly from a high NFC and suffer considerably from a low NFC. 4 This effect is particularly strong for Study 1 (see Figure 9b).…”
Section: Interaction Effect Of Risk Propensity and Need For Cognitionmentioning
confidence: 85%
“…In this paper, we present two exploratory studies that show how an individual's personality characteristics of risk propensity and need for cognition influence behavior over increasing task experience in a game that models safety and security decisions. Our paper benefits from earlier conference presentations of this data [3,4]. Here, we add context and an analysis of timing bias in addition to the analysis of the payoff bias we observed.…”
Section: Introductionmentioning
confidence: 96%
“…Risk taking was a stronger predictor of cookie acceptance than impulsivity in this study. Risk taking has been found to be a predictor of other security behaviors (see Grossklags and Reitter, 2014 ). This supports findings by Zeelenberg et al (1996) that risk takers are less likely to be concerned about the repercussions of their actions and less likely to consider any subsequent regret.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research also suggests that personality factors may interact with social manipulations to influence decision-making as personality traits may often affect behavior indirectly through influencing normative determinants of behavior ( Rosenstock, 1974 ; Ajzen, 1991 ). In the security and privacy domains, a range of candidate personality traits can be identified that are likely to affect decision-making, including impulsivity, risk-taking/risk propensity ( Grossklags and Reitter, 2014 ), willingness to self-disclose information about oneself, and sociability. These are described in more detail below.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al consider limited resources with an upper bound on the frequency of moves and analyze Nash Equilibria in this setting [25]. Several games study human defenders players against automated attackers using Periodic strategies [20,8,18]. All of this work uses exclusively non-adaptive players, often limiting analysis to solely opponents playing periodically.…”
Section: Related Workmentioning
confidence: 99%